Trends in Constructivist-Based Independent Curriculum Implementation: A Systematic Review - Tri Murwaningsih; Muna Fauziah (Attractive : Innovative Education Journal, 2025)
This research uses a systematic literature review method according to PRISMA 21 rules Scopus and Google Scholar databases from 2019 to 2023 are used as data sources. PRISMA guidelines consist of four phases: identification, screening, and data item determination. PRISMA is relevant to this research because PRISMA presents complete and detailed steps for conducting a literature review. Out of a total of 2017 collected articles, only 69 articles met the specified criteria. The inclusion criteria in this research are article publications from 2019 to 2023, publications in journals and proceedings, and articles published in Scopus and Sinta journals. Meanwhile, the exclusion criteria for this research are article publications since the implementation of the independent curriculum in journals and proceedings that have been indexed by Scopus and/or Sinta. All of these articles’ content were analyzed. The research findings show there is a significant increase in research trends about constructivist-based independent curriculum implementation from 2019 to 2023. Qualitative methods dominate, and various scientific disciplines have applied the constructivist approach in independent curricula. Constructivist-based independent curriculum implementation gives a positive impact on achievement, creativity, character, and student learning independence. Based on these findings, this research provides a scientific contribution as a foundation for policymakers to develop similar research by utilizing types of research, educational levels, and fields of study that are rarely explored